2020
DOI: 10.1186/s40359-020-00482-6
|View full text |Cite
|
Sign up to set email alerts
|

Decision-making inflexibility in a reversal learning task is associated with severity of problem gambling symptoms but not with a diagnosis of substance use disorder

Abstract: Background Decisions made by individuals with disordered gambling are markedly inflexible. However, whether anomalies in learning from feedback are gambling-specific, or extend beyond gambling contexts, remains an open question. More generally, addictive disorders—including gambling disorder—have been proposed to be facilitated by individual differences in feedback-driven decision-making inflexibility, which has been studied in the lab with the Probabilistic Reversal Learning Task (PRLT). In this task, partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 52 publications
(58 reference statements)
0
16
0
Order By: Relevance
“…Some studies using PRL tasks have reported higher perseverative responses after reversals supporting impaired cognitive flexibility in patients with SUD (3)(4)(5)(6)(7). However, available studies have not revealed robust and consistent findings as some studies have failed to evidence higher perseverative responses in patients with alcohol use disorder (AUDP) (8,9) as well as in amphetamine (3), cocaine (10), and methamphetamine (11) use disorder patients compared to controls. The reasons for the heterogeneity in these findings are unclear but may be partly due to differences in the clinical characteristics of the sample such as stage of addiction, psychiatric comorbidity, and medication.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies using PRL tasks have reported higher perseverative responses after reversals supporting impaired cognitive flexibility in patients with SUD (3)(4)(5)(6)(7). However, available studies have not revealed robust and consistent findings as some studies have failed to evidence higher perseverative responses in patients with alcohol use disorder (AUDP) (8,9) as well as in amphetamine (3), cocaine (10), and methamphetamine (11) use disorder patients compared to controls. The reasons for the heterogeneity in these findings are unclear but may be partly due to differences in the clinical characteristics of the sample such as stage of addiction, psychiatric comorbidity, and medication.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with GD, in comparison, show difficulties in learning novel stimulus-outcome associations following contingency changes during reversal learning (Jara-Rizzo et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted March 8, 2023. ; https://doi.org/10.1101/2023.03.06.531272 doi: bioRxiv preprint Patients with GD, in comparison, show difficulties in learning novel stimulus-outcome associations following contingency changes during reversal learning (Jara-Rizzo et al 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations